Science in mobile apps for education: tackling online learning within pandemic outbreak - Kamarudin, Nhidayu; Ong, Eileen; Chung, WS (International Journal of Engineering and Technology, 2020)
In adapting the issues of pandemic, educational sectors in Malaysia from the lower school level till university levels are encouraged to forecast any specific tools that may help in cater the needs in utilizing online learning. It is by right the issues that been face by global outbreak for everyone on earth as Covid19 that embarked big challenges in face to face and normal daily classes and learning method. Therefore this paper is written to give a general overview, uncover the possible models in used and technologies that may overcome the needs of online education specifically focused for improving the usage of online educational tools especially with the use of mobile ap-plication for learning itself. The concept of manual for pen and paper reporting can makes the reporting very slow especially in terms of communication and sharing of information. Plus, within the outbreak patterns may will provide inaccurate information and may also late results to be achieved. This paper is discussing model in plan and the implementation proposed with overcome results of the post results questionnaire conducted to get the major feedback on usage of the current proposed app.Â Â Â